Production of biodiesel from rubber seed - Karthik, Vasutheavan (2012)
The objective of this research is to produce biodiesel from rubber seed oil.Rubber seed oil(RSO)was obtained from rubber seed by soxhlet and microwave assisted extraction methods.Hexane was used as a solvent in the soxhlet extraction process.The yield of oil from rubber seed by soxhlet extraction method was found to be higher (34 – 40%) than by the microwave extraction method(30 – 32%).The physic-chemical properties of the RSO was measured and it was found that the RSO contained 22 wt.% of free fatty acids (FFA).The viscosity of the oil was found as 33.2 cm2/s at 40oC. Biodiesel was prepared by two-step method,where in the first step,the FFA was converted to fatty acid ethyl ester(FAEE)by acid catalyzed esterification,and in the second step the triglycerides(TG)was converted to FAEE by base catalyzed transesterification.Effect of different parameters,such as ethanol/oil molar ratio,temperature, catalyst concentration had been studied for both steps.In the first step,which is acid catalyzed esterification,the optimum parameters were found as 1:6 molar ratio of oil to ethanol,0.5% of catalyst (H2SO4) and at 50oC.The product from the first step was separated in a separating funnel to draw off the excess alcohol,catalyst and water.The optimum parameters for the second step were as follows: 1:6 molar ratio of oil to ethanol,0.5wt.% of catalyst (NaOH) and temperature of 50oC.After gravity separation of biodiesel from the glycerene layer,it was washed with hot water until a translucent product was obtained.The biodiesel was dried in the rotary vacuum evaporator at 100C for 1 h and the product was characterized.The viscosity of the final biodiesel was found as 5.92 cm2/s and FFA content was undetectable.The gas chromatography analysis shows that the amount of methyl ester found in the sample is quite high.